DHA Supplementation during Pregnancy and Lactation Affects Infants' Cellular but Not Humoral Immune Response - Esther Granot; Einat Jakobovich; Ruth Rabinowitz; Paloma Levy; Michael Schlesinger (Mediators of Inflammation)
Background. It is currently recommended that diet of pregnant mothers contain 200–300 mg DHA/day. Aim. To determine whether DHA supplementation during pregnancy and lactation affects infants' immune response. Methods. 60 women in ≥3rd pregnancy studied; 30 randomly assigned to receive DHA 400 mg/day from 12th week gestation until 4 months postpartum. From breast-fed infants, blood obtained for anti-HBs antibodies, immunoglobulins, lymphocyte subset phenotyping, and intracellular cytokine production. Results. CD4+ lymphocytes did not differ between groups, but CD4CD45RA/CD4 (naïve cells) significantly higher in infants in DHA+ group. Proportion of CD4 and CD8 cells producing IFNγ significantly lower in DHA+ group, with no differences in proportion of IL4-producing cells. Immunoglobulins and anti-HBs levels did not differ between groups. Conclusions. In infants of mothers receiving DHA supplementation, a higher percentage of CD4 naïve cells and decreased CD4 and CD8 IFNγ production is compatible with attenuation of a proinflammatory response.